Bioethanol Production from Paper Fibre Residue Using Diluted Alkali Hydrolysis and the Fermentation Process - G. Sathya Geetha; A. Navaneetha Gopalakrishnan (E-Journal of Chemistry)
The state of art for the bioethanol production from paper fibre residue using diluted alkali hydrolysis and fermentation processes was evaluated. Hydrolysis of paper fibre residue with diluted sodium hydroxide at various time period, temperature and concentration were investigated. The paper fibre residue was pre-steamed, impregnated with diluted NaOH (0 to 25%) and subsequently hydrolyzed in a reactor at temperatures that ranged between 30 to 50 oC, for reaction time between 30 minutes to 150 minutes. The highest yield of monosaccharide (indicating the efficient hydrolysis of cellulose and hemi cellulose) was found at a temperature of 35 oC for a reaction time of 90 minutes. Fermentability of hemicelluloses hydrolysate was tested using monosaccharide fermenting microorganism Penicillium chrysogenum and Saccharomyces cereviacea. The fermentability of the hydrolysate decreased strongly for hydrolysate produced at temperature higher than 50 oC. The ethanol concentration of monosaccharide hydrolysate was found to be 34.06 g/L and the ethanol yield was 0.097 g/g.